Use of Cerium(IV) in Potentiometric Titration of Norfloxacin in Pharmaceutical Preparations - Mandil, Hasna; Alhaj Sakur, Amer; Nasser, Bassam (Asian Journal of Chemistry, 2012)
An accurate potentiometric titration is proposed for the determination of norfloxacin (NRF) in pure drug and in its dosage forms. This method was based on the oxidation reaction of norfloxacin with cerium(lV) in 0.3 M HCl. The reaction was found to be quantitative with stoichiometry 1:4 (norfloxacin: Ce4+) and the methods are applicable over the range 20-1000 μg mL-1 (0.063-3.13 mM). The limits of quantifying was about 20 μg mL-1 (0.063 mM). The relative standard deviation did not exceed of ± 5.6 % and ± 4.8 % using potentiometric and differential Potentiometric titrations respectively. There for the proposed methods can be used for routine determination of norfloxacin in pharmaceutical formulations with high accurate. The proposed method was successfully applied to the determination of norfloxacin in pharmaceutical preparations and the results have been statistically compared with the spectrophotometric methods.